2022
DOI: 10.1007/s00520-022-07124-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of alpha-lipoic acid in counteracting paclitaxel- and doxorubicin-induced toxicities: a randomized controlled trial in breast cancer patients

Abstract: Background and objective Paclitaxel and doxorubicin are associated with neurotoxicity and cardiotoxicity respectively. This study aimed at investigating the role of alpha-lipoic acid (ALA) in counteracting paclitaxel-induced neuropathy and doxorubicin-associated cardiotoxicity in women with breast cancer. Patients and methods This randomized double-blind placebo-controlled prospective study included 64 patients with breast cancer who were randomized into c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 45 publications
1
9
0
1
Order By: Relevance
“…This is conceivably linked to chemotherapy side effects and development of neuropathy. Worsening in patients' QoL with chemotherapy, comparable to that reported in the present study, was previously reported when breast cancer patients administered taxanes 37,38 . Cilostazol administration was linked to less worsening effects in patients' QoL.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This is conceivably linked to chemotherapy side effects and development of neuropathy. Worsening in patients' QoL with chemotherapy, comparable to that reported in the present study, was previously reported when breast cancer patients administered taxanes 37,38 . Cilostazol administration was linked to less worsening effects in patients' QoL.…”
Section: Discussionsupporting
confidence: 89%
“…TA B L E 1 (Continued) NCI-CTCAE neuropathy grading, a valid patient reported outcome measure, 36 this approach was widely used in similar clinical trials assessing other different pharmacological interventions. 37,38 Our results were in favor of the preventive role of cilostazol at which the incidence of grade 2 or 3 neuropathy reported by our patients was 40% in the cilostazol arm compared to 86.7% in the placebo arm (p < 0.001). There was also longer time to develop symptoms of neuropathy in the cilostazol arm over the control arm.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Dietary changes do not alter nutrient levels in tumors and healthy tissues in a balanced manner. Further, similar to new drug combinations, the combination of dietary nutrients and DOX must be adapted based on the specific tumor and its metabolic activity, and clinical trials are required before an optimal anticancer regimen may be identified [ 111 ]. Here, we summarize the specific mechanisms by which vitamins, fatty acids, glucose analogs, and the micronutrient selenium regulate DIC and DOX resistance via p53.…”
Section: Nutrients Can Attenuate Dox Toxicity and Drug Resistance By ...mentioning
confidence: 99%
“…In addition, a-lipoic acid (a-LA), considered as a B vitamin because of the similarity in structure and function, was reported to play important roles in peripheral neuropathy because of nerve injury [27], T2DM [28,29], CIPN by various drugs [30][31][32]. a-LA may exert its neuroprotection through reducing oxidative stress, neuronal apoptosis [29], and the axon demyelination, protecting axons from demyelination [33 & ], and accelerating the process of nerve healing [27].…”
Section: Combination Of B Vitaminsmentioning
confidence: 99%